Effective Learning Outcomes Assessment: The Case of the MIS Department at the UoS - Nadia Rifaat; Waleed M. Al Sabhan .; Mohammed Nour . (Journal of Education and Vocational Research, 2012)
Accrediting organizations now mandate the development of learning outcomes (LO) and the methods to assess those learning outcomes for national and international institutions of higher learning. Because of this, academic institutions pay greater attention to the development and assessment of these LO. There are two types of learning outcomes: course outcomes and program outcomes. This paper presents an empirical study that examines both kinds of LO in a case study of one course (title: Database Fundamental and Applications, number: 0303331) within the Management Information System (MIS) department at the University of Sharjah (UoS), United Arab Emirates and presents the following with regard to this case study: 1) the development process of the LO for this specific course; 2) the data collection process, and 3) the data collected related to the assessment instruments for both the course and program LO (course learning instructions, course exams, course projects, students’ records, students’ grades, course reports, course evaluation, instructor evaluation, exit surveys, employer surveys, and job placement indicators); 4) the methods of assessment of the LO based on the analysis of the collected data using a variety of analysis technique and tools; and 5) the usage of the analysis results in successive semesters in order to improve the MIS courses and program. The findings of this empirical study suggest several areas for improvement. One improvement is the addition of more practice-based learning components. Additionally, the study shows that the enhancement of the course material, the improvement of teaching strategies, and the usage of technology and its infusion into the learning process are areas that can improve LO. Overall, the method of LO development and assessment described in this empirical examination has shown a positive effect on the courses and program in the MIS department, and it is believed that the results can be generalized for use by others in developing and assessing LO in other learning institutions.